Language and Ecology in the Classroom: A Study of Environmental Discourse in Balinese Primary School Textbooks - PARTHAMA, I GUSTI NGURAH; Giri, Ni Luh Kade Yuliani; Setianingsih, Ni Ketut Alit Ida (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 32 No 1 (2025): MaretDO - 10.24843/ling.2025.v32.i01.p09, 2025)
The study explores the integration of ecolinguistics perspectives into Balinese language education by analyzing environmental themes embedded in sixth-grade primary school textbooks. The objective is to examine ecological concepts that are conveyed through linguistic units, specifically words and phrases, in the context of local language instruction. Employing a qualitative descriptive approach, the study analyzes three texts selected from the textbooks. Each represents different aspects of environmental education: waste management, environmental stewardship, and ecological responsibility. Data were collected through documentation methods and analyzed using semantic and contextual interpretation. It emphasizes the identification of positive and negative ecological associations. The results reveal that the textbooks contain a wide range of Balinese lexical and phrasal units related to environmental issues with clear semantic links to ecological concepts. These linguistic expressions do not only support language acquisition, but also foster ecological awareness and ethical reflection among students. The findings demonstrate that Balinese language learning materials can effectively promote environmental values when designed with ecolinguistics insights. The study contributes to the growing body of research on ecolinguistics in education and suggests the strategic role of local languages in cultivating sustainable environmental attitudes.